Approaching critical pedagogies in education. - O'Toole, Barbara; Joseph, Ebun; Nyaluke, David (Routledge, 2020)
This opening chapter sets the scene for subsequent contributions. It begins with an examination of typical perceptions of ‘Africa’ in Northern classrooms and contexts. This is followed by an interrogation of ‘development education’ (DE) as it is currently conceptualised and enacted in Ireland. We argue for a ‘critical’ form of DE, one grounded in an understanding of political, economic, and historical processes. We draw attention to how discourses created before and during colonialism led to and perpetuate the dominance of Northern/White worldviews. These processes continue to impact on contemporary power dynamics between North and South and find their way into the curricula and pedagogy of Western schools. Challenging processes like these through countering such epistemic blindness is part of the work of these chapters. The conceptual framework for this introductory chapter, which provides the overall context for the book, draws from postcolonial and decolonial theorists, echoing the views of Stein and Andreotti (2016, p. 230), that “despite the formal decolonisation of much of the world, many elements of colonialism continue to contribute to the production of racial and cultural hierarchies”. We make the case here for ‘critical’ global education, one which involves recognition of historical processes and contemporary inequalities (including economic realities), which encompasses critical and political dimensions of thinking and practice, and which, in the process, impacts on race relations in the local context.
Keywords: Pedagogy; Education; Race; Research Subject Categories::SOCIAL SCIENCES; Diversity; initial teacher education; Global Justice